SOCIO-CULTURAL HERITAGE OF VICTORY IN THE GREAT PATRIOTIC WAR IN THE CONTEXT OF MODERN ETHICAL AND HISTORICAL REALITIES - Kasyanov, Valery; Davydova, Galina; Shilina, Natalya; Aleshin, Sergey; Volkova, Diana; Samygin, Sergey (Revista Inclusiones, 2019)
This article attempts to analyze the differences in the interpretation of Victory in the Great Patriotic War within the framework of the historical policy of the Soviet state, which gradually replaced the attitude to war and victory as real life experience, and the post-Soviet situation, characterized by the lack of consistent state memory policy accompanied, on the one hand, with spontaneous grassroots activity, the need for identity, and on the other hand, with political technology attempts to manipulate historical memory. The main content of the socio-cultural heritage of the victory in the Great Patriotic War is the preservation of the memory of the historical event of the heroism of the Soviet people in the victory over fascism that is large-scale for the peoples of the world.